Silicone rubber coating composite material, preparation method and application in automobile leather
By using modified silicone rubber coated composite materials in the surface layer of the automotive leather, the problem of existing automotive leather materials lacking flame retardancy is solved, and the safety and environmental protection of the automotive interior is improved.
Patent Information
- Application Number
- CN202411955527.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-04
AI Technical Summary
The existing automotive leather materials lack flame retardancy and are difficult to meet the safety and environmental protection needs of automotive interiors.
The silicone rubber coating composite material is used to improve its flame retardant, wear resistance and weather resistance by using modified materials and functional additives in the surface layer of the automotive leather. During the preparation of the modified material, materials such as chitosan, alumina and bentonite are used, and their dispersion and flame retardant properties are improved through fluorine modification and intercalation modification.
The produced automotive leather materials have good flame retardant, wear resistance and weather resistance. They are suitable for car seats, door panel decoration and other occasions, improving the safety and environmental protection of car interiors.
Smart Images

Figure CN119754043A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new material preparation, and specifically relates to a silicone rubber coating composite material, a preparation method and application in automobile leather. Background Art
[0002] With the rapid development of the automobile industry, the demand for automotive interior products with various functions is growing. Automotive leather is an important component of automobiles, directly related to the safety and comfort of drivers and passengers, and is also an important factor in improving the appearance and grade of automobiles. Automotive leather must achieve a perfect balance between consumers' visual aesthetics, environmental standards and interior quality. Therefore, in addition to meeting basic physical and chemical performance requirements, many automotive leathers also need to have good wear resistance, scratch resistance, flame retardancy, solvent resistance, anti-yellowing, as well as low fogging, low volatile organic compounds (VOC) and low odor.
[0003] In the use and manufacturing process of automobile leather, polymer materials of various raw materials have been developed and applied. For example, in the preparation method of automobile leather provided in patent document CN109811557A, a specific surface resin material is provided, which comprises the following components in parts by weight: 100 parts of waterborne polyurethane resin, 0.1 parts of defoaming agent, 0.4 parts of thickener, 0.2 parts of leveling agent, 2 parts of cross-linking agent, and 5 parts of waterborne color paste; the bottom solvent-free resin comprises the following components in parts by weight: 100 parts of 100% solid content polyurethane resin, 64-66 parts of isocyanate curing agent, 0.5 parts of foaming agent, and 0.5 parts of catalyst; the obtained automobile leather is used to make automobile interiors, and has good wear resistance, no odor, good antibacterial and antioxidant properties, but it does not have flame retardancy.
[0004] For example, in the automobile leather preparation process provided in patent document CN117002117A, a specific organic silicon surface layer is provided, which comprises the following raw materials in parts by weight: 10-40 parts of vinyl polydimethylsiloxane, 30-60 parts of vinyl MT silicone resin, 1-10 parts of methyl silicone resin, 1-15 parts of hydrogen-containing polysiloxane, 5-20 parts of silicone masterbatch, 0.1-10 parts of platinum catalyst, and 0.1-5 parts of inhibitor; the vinyl MT silicone resin comprises vinyl MT silicone resin-1, vinyl MT silicone Resin-2 and vinyl MT silicone resin-3; the weight average molecular weight of the vinyl MT silicone resin-1 is 2000-5000, the weight average molecular weight of the vinyl MT silicone resin-2 is 10000-15000, and the weight average molecular weight of the vinyl MT silicone resin-3 is 20000-25000; the mass fraction of vinyl in the vinyl MT silicone resin is 2%-5%; the prepared organic silicone automotive leather has good folding resistance, wear resistance, anti-fouling, seam fatigue and bite performance, and can be suitable for use in infants and young children. However, the above automotive leather is also not flame retardant.
[0005] In fact, flame retardancy, wear resistance, environmental protection and other properties are very important for automotive leather, therefore, the present invention is specially proposed. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a silicone rubber coating composite material, a preparation method and its application in automotive leather. The obtained silicone rubber coating composite material has excellent comprehensive properties such as flame retardancy, aging resistance and mechanical properties, and the obtained automotive leather is environmentally friendly and has excellent comprehensive performance.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a silicone rubber coating composite material, comprising the following preparation raw materials: 40 to 70 parts of methyl vinyl silicone rubber, 20 to 40 parts of high vinyl silicone rubber, 0.2 to 0.8 parts of organic peroxide, 2 to 8 parts of polyether modified polydimethylsiloxane, 5 to 15 parts of polyurethane elastomer, 8 to 25 parts of modified material, 1 to 5 parts of triethoxysilane, 2 to 8 parts of tackifier, 8 to 20 parts of D4H cyclotetrasiloxane, 0.1 to 1 part of platinum vulcanizer, and 0.1 to 0.5 part of dispersant.
[0009] As a preferred embodiment of the technical solution of the present invention, the preparation of the modified material comprises the following steps:
[0010] S1, chitosan is added to a sodium hydroxide solution, chloroacetic acid is added three times under heating and stirring conditions, and after the addition is completed, the heating temperature is maintained to continue the reaction. After the reaction is completed, the pH value of the system is adjusted to neutral and then precipitated with ethanol, and finally centrifuged, filtered, and dried to obtain carboxymethyl chitosan for standby use;
[0011] S2, adding aluminum nitrate nonahydrate to ethanol, stirring evenly, then adding ammonium fluoride and ethanolamine, reacting under heating conditions, and after the reaction is completed, first heating to remove excess ethanol, then sequentially carbonizing and calcining, and finally washing and drying to obtain pre-modified alumina;
[0012] S3, adding the pre-modified alumina obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating under stirring conditions for reaction. After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use;
[0013] S4, adding bentonite to water, stirring evenly under heating conditions, then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction, after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite;
[0014] S5. Add the modified bentonite obtained in step S4 into water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35-45°C for 1-4h, then add the modified alumina obtained in step S3, continue stirring and heating for 1-4h, after the treatment is completed, centrifuge, filter, dry, crush and sieve to obtain the modified material.
[0015] As a preferred embodiment of the technical solution of the present invention, in step S1, the concentration of the sodium hydroxide solution is 30-50wt%;
[0016] The usage ratio of chitosan, sodium hydroxide solution and total amount of chloroacetic acid is 10g:90-150mL:40-60g;
[0017] The three additions of chloroacetic acid were added in equal amounts;
[0018] The heating temperature is 50-70°C and the reaction time is 2-6h.
[0019] As a preferred embodiment of the technical solution of the present invention, in step S2, the usage ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10 g: 40-80 mL: 0.3-0.5 g: 1-2.5 g;
[0020] The heating reaction temperature is 60-80°C and the reaction time is 3-10h;
[0021] The carbonization temperature is 250-260°C and the carbonization time is 0.5-2h;
[0022] The calcination temperature is 990-1050°C, and the calcination time is 0.5-4h.
[0023] As a preferred embodiment of the technical solution of the present invention, in step S3, the amount ratio of pre-modified alumina, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1 g: 20-30 g: 0.8-1.5 mL;
[0024] The heating reaction temperature is 85-95°C, and the heating reaction time is 0.5-5h.
[0025] As a preferred embodiment of the technical solution of the present invention, in step S4, the usage ratio of bentonite, water and tri-n-butyl phosphate is 10 g: 120-200 mL: 3.5-5.5 g;
[0026] The heating temperature is 70-85°C, and the stirring reaction time is 6-12 hours.
[0027] As a preferred embodiment of the technical solution of the present invention, in step S5, the mass ratio of modified bentonite, water, carboxymethyl chitosan, and modified alumina is 1:10-15:0.2-0.35:0.5-0.8;
[0028] Sieve through 80-150 mesh.
[0029] In a second aspect, the present invention hopes to provide the use of the above silicone rubber coating composite material in the preparation of automobile leather.
[0030] Specifically, the present invention also provides a method for preparing automobile leather, comprising the following steps:
[0031] (1) After the silicone rubber coating composite material is evenly mixed, the mixture is heated to 100-150 g / m 2 The amount is evenly coated on the release paper, and then baked in an oven to reach a semi-vulcanized state to obtain a coating surface layer;
[0032] (2) Mix the filling layer formula evenly and add 120-180g / m 2 The amount of the coating is evenly applied to the surface of the coating obtained in step (1), and then baked in an oven to reach a semi-vulcanized state to obtain a filling layer;
[0033] (3) Mix the bonding layer formula evenly and add 180-250g / m 2 The amount of the filling layer is evenly coated on the surface of the filling layer obtained in step (2), and after being baked in an oven, one side of the filling layer is bonded to the microfiber fabric, and after being baked again, it is completely vulcanized;
[0034] (4) After the vulcanization is complete, the release paper is separated by a reeling machine to obtain the automotive leather product.
[0035] As a preferred embodiment of the technical solution of the present invention, in step (1), the length of the oven is 10 m, the temperature of the four zones is 60° C., and the baking time is 2 min;
[0036] In step (2), the filling layer formula includes the following raw materials, measured in parts by weight: 80-120 parts of methyl vinyl silicone rubber, 40-50 parts of fumed silica, 8-15 parts of hexamethylcyclotrisilazane, 2-8 parts of polyether modified polydimethylsiloxane, 0.2-1 parts of organic peroxide, 1-3 parts of triethoxysilane, 0.1-0.2 parts of white spirit, 0.1-0.2 parts of decanate, 0.5-1 parts of matting powder, and 0.08-0.2 parts of dispersant;
[0037] The oven length is 15m, the temperature of the four zones is 80℃, and the baking time is 2min;
[0038] In step (3), the laminating layer formula includes the following raw materials, in parts by weight: 80-120 parts of methyl vinyl silicone rubber, 40-50 parts of fumed silica, 8-15 parts of hexamethylcyclotrisilazane, 2-8 parts of polyether modified polydimethylsiloxane, 0.1-1 parts of organic peroxide, 1-3 parts of triethoxysilane, 0.1-0.2 parts of white spirit, 0.1-0.2 parts of decanate, 0.1-1 parts of platinum vulcanizing agent, 0.5-1 parts of matting powder, 0.5-1 parts of tackifier, and 0.08-0.2 parts of dispersant;
[0039] The oven length after coating the laminating layer formula is 5m, the temperature of the four zones is 75°C, and the baking time is 30s;
[0040] The length of the oven for the second baking is 35m, the baking temperatures in the five zones are 100°C, 100°C, 110°C, 120°C, and 130°C, and the baking time is 5min.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] (1) The present invention provides a silicone rubber coating composite material, which is used to prepare the surface layer of automobile leather, so that the prepared automobile leather has good wear resistance, flame retardancy, weather resistance and other effects.
[0043] (2) The automotive leather material provided by the present invention uses ultra-high molecular polymer fiber (ultra-fiber) as the base fabric, and is coated with a bonding layer, a filling layer and a surface layer in sequence, wherein the bonding layer can make the ultra-fiber base fabric better fit with the filling layer, and the filling layer can enhance the softness, thickness and wear resistance of the hand feel; the surface layer has the effects of flame retardancy, wear resistance and weather resistance; the layers are used in conjunction with each other, so that the prepared automotive leather is suitable for applications in occasions such as automobile seats and door panel decorations.
[0044] (3) The rubber coating composite material provided by the present invention uses silicone rubber as the main material, and other functional additives, especially modified materials, are added to make the composite material have good comprehensive performance. In the preparation process of the modified material, chitosan, alumina and bentonite are used as the main raw materials, among which chitosan can improve the wear resistance of the composite surface layer, and its good absorbency can improve the barrier performance of automobile leather; alumina itself is a very good flame retardant particle, and can also improve the hardness, tear resistance and wear resistance of rubber; bentonite can improve the mechanical strength, heat resistance and aging resistance of the rubber coating composite material. In the actual processing process, in order to improve the use effect of the above particles, the present invention performs a simple carboxyl modification on chitosan, improves the compatibility of chitosan and introduces carboxyl groups to facilitate subsequent composite effects; alumina, as an inorganic filler particle, has the disadvantage of poor dispersibility, so the present application sequentially performs fluorine modification and 3-(triethoxysilyl)propyl succinic anhydride modification on alumina, and fluorine modification improves the dispersibility of alumina while also The flame retardancy of the composite material can be further improved. The introduced fluorine element can also form hydrogen bonds with the hydroxyl and carboxyl groups of chitosan and bentonite to improve the composite effect. The carboxyl groups introduced by 3-(triethoxysilyl)propyl succinic anhydride further enrich the groups on the surface of alumina to further improve the composite effect. Bentonite, as a layered clay, has poor dispersibility, so it is often subjected to intercalation modification. The present application specifically selects tri-n-butyl phosphate for intercalation modification because tri-n-butyl phosphate is a commonly used flame retardant, which can further improve the flame retardancy of the composite material. At the same time, the phosphorus element of tri-n-butyl phosphate can form hydrogen bonds with the aminocarboxyl groups of chitosan and the carboxyl groups of alumina. The formed filler network is beneficial to improving the stability, heat resistance, flame retardancy, barrier properties, mechanical properties, etc. of the rubber coating composite material, thereby improving the performance of automotive leather. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a product schematic diagram of the automotive leather prepared in Example 4. DETAILED DESCRIPTION
[0046] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0047] Unless otherwise specified, the chemical reagents and production equipment involved in the present invention are purchased from the market.
[0048] Silicone rubber coating composite materials:
[0049] Methyl vinyl silicone rubber, brand XHG-110-1, purchased from Zhejiang Xin'an Chemical Group Co., Ltd.;
[0050] High vinyl silicone rubber, also methyl vinyl silicone rubber, with relatively high vinyl content, brand XHG-110-9, purchased from Zhejiang Xin'an Chemical Group Co., Ltd.;
[0051] Organic peroxides, including dihydropropane peroxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, etc., with the brand name TNOF-50M, were purchased from Dongguan Tianan Silica Gel Co., Ltd.;
[0052] Polyether modified polydimethylsiloxane, brand SH204, purchased from Hubei Longsheng Sihai New Materials Co., Ltd.;
[0053] Polyurethane elastomer, brand 86, purchased from DSM of the Netherlands;
[0054] Triethoxysilane, brand C8145, purchased from Dongguan Tianan Silica Gel Co., Ltd.;
[0055] Tackifier, terpene-styrene resin, brand KH-792, purchased from Dongguan Dinghai Plastic Chemical Co., Ltd.;
[0056] D4H cyclotetrasiloxane, purchased from Dongguan Tianan Silica Gel Co., Ltd.;
[0057] Platinum curing agent, brand name TNA-25PS, purchased from Dongguan Tianan Silicone Co., Ltd.;
[0058] The dispersant was casein, purchased from Guangdong Zhongtai Lianhua New Materials Co., Ltd.
[0059] In the filling layer formula:
[0060] Methyl vinyl silicone rubber, brand XHG-110-1, purchased from Zhejiang Xin'an Chemical Group Co., Ltd.;
[0061] Hexamethylcyclotrisilazane was purchased from Dongguan Beiteli New Materials Co., Ltd.
[0062] Polyether modified polydimethylsiloxane, brand SH204, purchased from Hubei Longsheng Sihai New Materials Co., Ltd.;
[0063] Organic peroxides, including dihydropropane peroxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, etc., with the brand name TNOF-50M, were purchased from Dongguan Tianan Silica Gel Co., Ltd.;
[0064] Triethoxysilane, brand C8145, purchased from Dongguan Tianan Silica Gel Co., Ltd.;
[0065] Matting powder, made of silicon dioxide, silicate, and talc, was purchased from Shenzhen Xingsheng Pearlescent Chemical Pigment Co., Ltd.;
[0066] The dispersant was casein, purchased from Guangdong Zhongtai Lianhua New Materials Co., Ltd.
[0067] In the laminating layer formula:
[0068] Methyl vinyl silicone rubber, brand XHG-110-1, purchased from Zhejiang Xin'an Chemical Group Co., Ltd.;
[0069] Hexamethylcyclotrisilazane was purchased from Dongguan Beiteli New Materials Co., Ltd.
[0070] Polyether modified polydimethylsiloxane, brand SH204, purchased from Hubei Longsheng Sihai New Materials Co., Ltd.;
[0071] Organic peroxides, including dihydropropane peroxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, etc., with the brand name TNOF-50M, were purchased from Dongguan Tianan Silica Gel Co., Ltd.;
[0072] Triethoxysilane, brand C8145, purchased from Dongguan Tianan Silica Gel Co., Ltd.;
[0073] Platinum curing agent, brand name TNA-25PS, purchased from Dongguan Tianan Silicone Co., Ltd.;
[0074] Matting powder, made of silicon dioxide, silicate, and talc, was purchased from Shenzhen Xingsheng Pearlescent Chemical Pigment Co., Ltd.;
[0075] Tackifier, terpene-styrene resin, brand KH-792, purchased from Dongguan Dinghai Plastic Chemical Co., Ltd.;
[0076] The dispersant was casein, purchased from Guangdong Zhongtai Lianhua New Materials Co., Ltd.
[0077] The microfiber grey cloth is a composite of polyamide, carbon fiber and resin, with the brand name F7, purchased from Huafeng Microfiber Co., Ltd.
[0078] The deacetylation degree of chitosan was about 85%, and it was purchased from Shandong Yatu Biotechnology Co., Ltd.
[0079] Bentonite was purchased from Shanghai Aladdin Reagent Co., Ltd.
[0080] In the present invention, unless otherwise specified, the "parts" are all parts by weight. The parts referred to in the embodiments may be specific weights, or may be reduced or increased in equal proportions.
[0081] Example 1
[0082] A rubber coating composite material comprises the following raw materials: 50 parts of methyl vinyl silicone rubber, 30 parts of high vinyl silicone rubber, 0.5 parts of organic peroxide, 5 parts of polyether modified polydimethylsiloxane, 10 parts of polyurethane elastomer, 18 parts of modifying material, 2 parts of triethoxysilane, 5 parts of tackifier, 15 parts of D4H cyclotetrasiloxane, 0.2 parts of platinum vulcanizer and 0.15 parts of dispersant.
[0083] Wherein, the preparation of the modified material comprises the following steps:
[0084] S1, chitosan was added to a 40wt% sodium hydroxide solution, and chloroacetic acid was added in equal amounts three times under heating and stirring conditions (55°C). After the addition was completed, the heating temperature was maintained to continue the reaction (55°C, 4h). After the reaction was completed, the pH value of the system was adjusted to neutral and then precipitated with ethanol. Finally, carboxymethyl chitosan was obtained by centrifugation, suction filtration, and drying, and the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid was 10g:110mL:48g.
[0085] S2. Aluminum nitrate nonahydrate is added to ethanol, and ammonium fluoride and ethanolamine are added after stirring, and the reaction is carried out under heating conditions (70°C, 6h). After the reaction is completed, the temperature is first raised to remove excess ethanol, and then carbonization (255°C, 1h) and calcination (1000°C, 1.5h) are carried out in sequence, and finally washing and drying are carried out to obtain pre-modified alumina; wherein the amount ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10g:55mL:0.4g:1.6g;
[0086] S3, adding the pre-modified alumina obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating the reaction under stirring conditions (85°C, 2h). After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use; the amount ratio of pre-modified alumina, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1g:25g:1.2mL;
[0087] S4, adding bentonite to water, stirring evenly under heating conditions (75°C), then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction (75°C, 8h), after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite; the amount ratio of bentonite, water, and tri-n-butyl phosphate is 10g:150mL:4.5g;
[0088] S5. Add the modified bentonite obtained in step S4 into water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35°C for 2h, then add the modified alumina obtained in step S3, continue stirring and heating for 2.5h, after the treatment is completed, centrifuge, filter, dry, crush and sieve 100 mesh to obtain a modified material; wherein the mass ratio of modified bentonite, water, carboxymethyl chitosan and modified alumina is 1:12:0.25:0.65.
[0089] Example 2
[0090] A rubber coating composite material comprises the following raw materials: 48 parts of methyl vinyl silicone rubber, 35 parts of high vinyl silicone rubber, 0.6 parts of organic peroxide, 5.5 parts of polyether modified polydimethylsiloxane, 9.5 parts of polyurethane elastomer, 17.5 parts of modifying material, 0.5 parts of triethoxysilane, 4.8 parts of tackifier, 12 parts of D4H cyclotetrasiloxane, 0.2 parts of platinum vulcanizer and 0.15 parts of dispersant.
[0091] Wherein, the preparation of the modified material comprises the following steps:
[0092] S1, chitosan was added to a 40wt% sodium hydroxide solution, and chloroacetic acid was added in equal amounts three times under heating and stirring conditions (55°C). After the addition was completed, the heating temperature was maintained to continue the reaction (55°C, 4h). After the reaction was completed, the pH value of the system was adjusted to neutral and then precipitated with ethanol. Finally, carboxymethyl chitosan was obtained by centrifugation, suction filtration, and drying, and the chitosan was used for standby use; wherein the amount ratio of chitosan, sodium hydroxide solution, and the total amount of chloroacetic acid was 10g:110mL:50g;
[0093] S2. Aluminum nitrate nonahydrate is added to ethanol, and after stirring, ammonium fluoride and ethanolamine are added, and the reaction is carried out under heating conditions (70°C, 6h). After the reaction is completed, the temperature is first raised to remove excess ethanol, and then carbonization (260°C, 0.5h) and calcination (1000°C, 1.5h) are carried out in sequence, and finally washing and drying are carried out to obtain pre-modified alumina; wherein the amount ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10g:60mL:0.4g:1.55g;
[0094] S3, adding the pre-modified alumina obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating reaction (85°C, 2h) under stirring. After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use; the amount ratio of pre-modified alumina, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1g:25g:1.3mL;
[0095] S4, adding bentonite to water, stirring evenly under heating conditions (75°C), then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction (75°C, 7h), after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite; the amount ratio of bentonite, water, and tri-n-butyl phosphate is 10g:150mL:4.2g;
[0096] S5. Add the modified bentonite obtained in step S4 into water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35°C for 2h, then add the modified alumina obtained in step S3, continue stirring and heating for 3h, after the treatment is completed, centrifuge, filter, dry, crush and sieve 100 mesh to obtain a modified material; wherein the mass ratio of modified bentonite, water, carboxymethyl chitosan and modified alumina is 1:12:0.27:0.6.
[0097] Example 3
[0098] A rubber coating composite material comprises the following raw materials: 52 parts of methyl vinyl silicone rubber, 28 parts of high vinyl silicone rubber, 0.55 parts of organic peroxide, 6 parts of polyether modified polydimethylsiloxane, 10.5 parts of polyurethane elastomer, 18.5 parts of modifying material, 0.5 parts of triethoxysilane, 5.2 parts of tackifier, 12 parts of D4H cyclotetrasiloxane, 0.2 parts of platinum vulcanizer and 0.15 parts of dispersant.
[0099] Wherein, the preparation of the modified material comprises the following steps:
[0100] S1, chitosan was added to a 40wt% sodium hydroxide solution, and chloroacetic acid was added in equal amounts three times under heating and stirring conditions (60°C). After the addition was completed, the heating temperature was maintained to continue the reaction (60°C, 3h). After the reaction was completed, the pH value of the system was adjusted to neutral and then precipitated with ethanol. Finally, carboxymethyl chitosan was obtained by centrifugation, suction filtration, and drying, and the chitosan was used for standby use; wherein the amount ratio of chitosan, sodium hydroxide solution, and the total amount of chloroacetic acid was 10g:110mL:50g;
[0101] S2. Aluminum nitrate nonahydrate is added to ethanol, and ammonium fluoride and ethanolamine are added after stirring, and the reaction is carried out under heating conditions (72°C, 7h). After the reaction is completed, the temperature is first raised to remove excess ethanol, and then carbonization (260°C, 0.5h) and calcination (1050°C, 1h) are carried out in sequence, and finally washing and drying are carried out to obtain pre-modified alumina; wherein the amount ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10g:60mL:0.4g:1.5g;
[0102] S3, adding the pre-modified alumina obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating reaction (80°C, 2h) under stirring. After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use; the amount ratio of pre-modified alumina, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1g:25g:1.2mL;
[0103] S4, adding bentonite to water, stirring evenly under heating conditions (75°C), then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction (80°C, 7h), after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite; the amount ratio of bentonite, water, and tri-n-butyl phosphate is 10g:150mL:4.4g;
[0104] S5. Add the modified bentonite obtained in step S4 into water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35°C for 2h, then add the modified alumina obtained in step S3, continue stirring and heating for 3h, after the treatment is completed, centrifuge, filter, dry, crush and sieve 100 mesh to obtain a modified material; wherein the mass ratio of modified bentonite, water, carboxymethyl chitosan and modified alumina is 1:12:0.25:0.6.
[0105] Example 4
[0106] A method for preparing automobile leather comprises the following steps:
[0107] (1) After the rubber coating composite material described in Example 1 is mixed uniformly, the mixture is heated to 120 g / m 2 The amount of the coating is evenly coated on the release paper, and then baked in an oven (the oven length is 10m, the temperature of the four zones is 60°C, and the baking time is 2min) to reach a semi-vulcanized state to obtain a coating surface layer;
[0108] (2) Mix the filling layer formula evenly and add 150g / m 2 The amount of the coating is evenly applied to the surface of the coating obtained in step (1), and then baked in an oven (the oven length is 15 m, the temperature of the four zones is 80° C., and the baking time is 2 min) to reach a semi-vulcanized state, thereby obtaining a filling layer;
[0109] (3) Mix the bonding layer formula evenly and add 200g / m 2The amount of the filling layer obtained in step (2) is evenly coated on the surface of the filling layer, and after being baked in an oven (the oven length is 5m, the temperature of the four zones is 75°C, and the baking time is 30s), one side of the filling layer is bonded (80kg heavy round pressure wheel, 2.5KG cylinder pressure) to the microfiber grey cloth, and baked again (the oven length is 35m, the baking temperatures of the five zones are 100°C, 100°C, 110°C, 120°C, and 130°C, respectively, and the baking time is 5min) to achieve complete vulcanization;
[0110] (4) After the vulcanization is complete, the release paper is separated by a reeling machine to obtain the automotive leather product.
[0111] Wherein, in step (2), the filling layer formula includes the following raw materials, measured in parts by weight: 100 parts of methyl vinyl silicone rubber, 45 parts of fumed silica, 10 parts of hexamethylcyclotrisilazane, 5 parts of polyether modified polydimethylsiloxane, 0.5 parts of organic peroxide, 2 parts of triethoxysilane, 0.15 parts of white oil, 0.15 parts of decanter, 0.8 parts of matting powder, and 0.1 parts of dispersant.
[0112] Wherein, in step (3), the formula of the bonding layer includes the following raw materials, measured in parts by weight: 100 parts of methyl vinyl silicone rubber, 45 parts of fumed silica, 10 parts of hexamethylcyclotrisilazane, 5 parts of polyether modified polydimethylsiloxane, 0.5 parts of organic peroxide, 2 parts of triethoxysilane, 0.15 parts of white spirit, 0.15 parts of decanate, 0.5 parts of platinum vulcanizer, 0.8 parts of matting powder, 0.5 parts of tackifier, and 0.1 parts of dispersant.
[0113] Example 5
[0114] A method for preparing automobile leather comprises the following steps:
[0115] (1) After the rubber coating composite material described in Example 2 is mixed evenly, the mixture is heated to 120 g / m 2 The amount of the coating is evenly coated on the release paper, and then baked in an oven (the oven length is 10m, the temperature of the four zones is 60°C, and the baking time is 2min) to reach a semi-vulcanized state to obtain a coating surface layer;
[0116] (2) Mix the filling layer formula evenly and add 150g / m 2 The amount of the coating is evenly applied to the surface of the coating obtained in step (1), and then baked in an oven (the oven length is 15 m, the temperature of the four zones is 80° C., and the baking time is 2 min) to reach a semi-vulcanized state, thereby obtaining a filling layer;
[0117] (3) Mix the bonding layer formula evenly and add 200g / m 2The amount of the filling layer obtained in step (2) is evenly coated on the surface of the filling layer, and after being baked in an oven (the oven length is 5m, the temperature of the four zones is 75°C, and the baking time is 30s), one side of the filling layer is bonded (80kg heavy round pressure wheel, 2.5KG cylinder pressure) to the microfiber grey cloth, and baked again (the oven length is 35m, the baking temperatures of the five zones are 100°C, 100°C, 110°C, 120°C, and 130°C, respectively, and the baking time is 5min) to achieve complete vulcanization;
[0118] (4) After the vulcanization is complete, the release paper is separated by a reeling machine to obtain the automotive leather product.
[0119] Wherein, in step (2), the filling layer formula includes the following raw materials, measured in parts by weight: 100 parts of methyl vinyl silicone rubber, 45 parts of fumed silica, 10 parts of hexamethylcyclotrisilazane, 5 parts of polyether modified polydimethylsiloxane, 0.5 parts of organic peroxide, 2 parts of triethoxysilane, 0.15 parts of white oil, 0.15 parts of decanter, 0.8 parts of matting powder, and 0.1 parts of dispersant.
[0120] Wherein, in step (3), the formula of the bonding layer includes the following raw materials, measured in parts by weight: 100 parts of methyl vinyl silicone rubber, 45 parts of fumed silica, 10 parts of hexamethylcyclotrisilazane, 5 parts of polyether modified polydimethylsiloxane, 0.5 parts of organic peroxide, 2 parts of triethoxysilane, 0.15 parts of white spirit, 0.15 parts of decanate, 0.5 parts of platinum vulcanizer, 0.8 parts of matting powder, 0.5 parts of tackifier, and 0.1 parts of dispersant.
[0121] Example 6
[0122] A method for preparing automobile leather comprises the following steps:
[0123] (1) After the rubber coating composite material described in Example 3 is mixed evenly, the mixture is heated to 120 g / m 2 The amount of the coating is evenly coated on the release paper, and then baked in an oven (the oven length is 10m, the temperature of the four zones is 60°C, and the baking time is 2min) to reach a semi-vulcanized state to obtain a coating surface layer;
[0124] (2) Mix the filling layer formula evenly and add 150g / m 2 The amount of the coating is evenly applied to the surface of the coating obtained in step (1), and then baked in an oven (the oven length is 15 m, the temperature of the four zones is 80° C., and the baking time is 2 min) to reach a semi-vulcanized state, thereby obtaining a filling layer;
[0125] (3) Mix the bonding layer formula evenly and add 200g / m 2The amount of the filling layer obtained in step (2) is evenly coated on the surface of the filling layer, and after being baked in an oven (the oven length is 5m, the temperature of the four zones is 75°C, and the baking time is 30s), one side of the filling layer is bonded (80kg heavy round pressure wheel, 2.5KG cylinder pressure) to the microfiber grey cloth, and baked again (the oven length is 35m, the baking temperatures of the five zones are 100°C, 100°C, 110°C, 120°C, and 130°C, respectively, and the baking time is 5min) to achieve complete vulcanization;
[0126] (4) After the vulcanization is complete, the release paper is separated by a reeling machine to obtain the automotive leather product.
[0127] Wherein, in step (2), the filling layer formula includes the following raw materials, measured in parts by weight: 100 parts of methyl vinyl silicone rubber, 45 parts of fumed silica, 10 parts of hexamethylcyclotrisilazane, 5 parts of polyether modified polydimethylsiloxane, 0.5 parts of organic peroxide, 2 parts of triethoxysilane, 0.15 parts of white oil, 0.15 parts of decanter, 0.8 parts of matting powder, and 0.1 parts of dispersant.
[0128] Wherein, in step (3), the formula of the bonding layer includes the following raw materials, measured in parts by weight: 100 parts of methyl vinyl silicone rubber, 45 parts of fumed silica, 10 parts of hexamethylcyclotrisilazane, 5 parts of polyether modified polydimethylsiloxane, 0.5 parts of organic peroxide, 2 parts of triethoxysilane, 0.15 parts of white spirit, 0.15 parts of decanate, 0.5 parts of platinum vulcanizer, 0.8 parts of matting powder, 0.5 parts of tackifier, and 0.1 parts of dispersant.
[0129] Comparative Example 1
[0130] Compared with Example 1, in the preparation process of the modifier of Comparative Example 1, step S1 is omitted, that is, chitosan is not modified. Specifically, Comparative Example 1 provides a rubber coating composite material, including the following preparation raw materials: 50 parts of methyl vinyl silicone rubber, 30 parts of high vinyl silicone rubber, 0.5 parts of organic peroxide, 5 parts of polyether modified polydimethylsiloxane, 10 parts of polyurethane elastomer, 18 parts of modifying material, 2 parts of triethoxysilane, 5 parts of tackifier, 15 parts of D4H cyclotetrasiloxane, 0.2 parts of platinum vulcanizer, and 0.15 parts of dispersant.
[0131] Wherein, the preparation of the modified material comprises the following steps:
[0132] S1, take chitosan and set aside;
[0133] S2. Aluminum nitrate nonahydrate is added to ethanol, and ammonium fluoride and ethanolamine are added after stirring, and the reaction is carried out under heating conditions (70°C, 6h). After the reaction is completed, the temperature is first raised to remove excess ethanol, and then carbonization (255°C, 1h) and calcination (1000°C, 1.5h) are carried out in sequence, and finally washing and drying are carried out to obtain pre-modified alumina; wherein the amount ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10g:55mL:0.4g:1.6g;
[0134] S3, adding the pre-modified alumina obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating the reaction under stirring conditions (85°C, 2h). After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use; the amount ratio of pre-modified alumina, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1g:25g:1.2mL;
[0135] S4, adding bentonite to water, stirring evenly under heating conditions (75°C), then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction (75°C, 8h), after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite; the amount ratio of bentonite, water, and tri-n-butyl phosphate is 10g:150mL:4.5g;
[0136] S5. Add the modified bentonite obtained in step S4 into water, stir evenly, then add the chitosan obtained in step S1, heat and stir at 35°C for 2h, then add the modified alumina obtained in step S3, continue stirring and heating for 2.5h, after the treatment is completed, centrifuge, filter, dry, crush and sieve 100 mesh to obtain a modified material; wherein the mass ratio of modified bentonite, water, carboxymethyl chitosan and modified alumina is 1:12:0.25:0.65.
[0137] Comparative Example 2
[0138] Compared with Example 1, in the preparation process of the modifier of Comparative Example 2, step S2 is omitted, that is, the aluminum oxide is not pre-modified. Specifically, Comparative Example 2 provides a rubber coating composite material, including the following preparation raw materials: 50 parts of methyl vinyl silicone rubber, 30 parts of high vinyl silicone rubber, 0.5 parts of organic peroxide, 5 parts of polyether modified polydimethylsiloxane, 10 parts of polyurethane elastomer, 18 parts of modifying material, 2 parts of triethoxysilane, 5 parts of tackifier, 15 parts of D4H cyclotetrasiloxane, 0.2 parts of platinum vulcanizer, and 0.15 parts of dispersant.
[0139] Wherein, the preparation of the modified material comprises the following steps:
[0140] S1, chitosan was added to a 40wt% sodium hydroxide solution, and chloroacetic acid was added in equal amounts three times under heating and stirring conditions (55°C). After the addition was completed, the heating temperature was maintained to continue the reaction (55°C, 4h). After the reaction was completed, the pH value of the system was adjusted to neutral and then precipitated with ethanol. Finally, carboxymethyl chitosan was obtained by centrifugation, suction filtration, and drying, and the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid was 10g:110mL:48g.
[0141] S2, take aluminum nitrate nonahydrate and set aside;
[0142] S3, adding the aluminum nitrate nonahydrate obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating reaction (85°C, 2h) under stirring conditions. After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use; the dosage ratio of aluminum nitrate nonahydrate, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1g:25g:1.2mL;
[0143] S4, adding bentonite to water, stirring evenly under heating conditions (75°C), then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction (75°C, 8h), after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite; the amount ratio of bentonite, water, and tri-n-butyl phosphate is 10g:150mL:4.5g;
[0144] S5. Add the modified bentonite obtained in step S4 into water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35°C for 2h, then add the modified alumina obtained in step S3, continue stirring and heating for 2.5h, after the treatment is completed, centrifuge, filter, dry, crush and sieve 100 mesh to obtain a modified material; wherein the mass ratio of modified bentonite, water, carboxymethyl chitosan and modified alumina is 1:12:0.25:0.65.
[0145] Comparative Example 3
[0146] Compared with Example 1, in the preparation process of the modifier of Comparative Example 3, step S3 is omitted, that is, the aluminum oxide is not modified. Specifically, Comparative Example 3 provides a rubber coating composite material, including the following preparation raw materials: 50 parts of methyl vinyl silicone rubber, 30 parts of high vinyl silicone rubber, 0.5 parts of organic peroxide, 5 parts of polyether modified polydimethylsiloxane, 10 parts of polyurethane elastomer, 18 parts of modifying material, 2 parts of triethoxysilane, 5 parts of tackifier, 15 parts of D4H cyclotetrasiloxane, 0.2 parts of platinum vulcanizer, and 0.15 parts of dispersant.
[0147] Wherein, the preparation of the modified material comprises the following steps:
[0148] S1, chitosan was added to a 40wt% sodium hydroxide solution, and chloroacetic acid was added in equal amounts three times under heating and stirring conditions (55°C). After the addition was completed, the heating temperature was maintained to continue the reaction (55°C, 4h). After the reaction was completed, the pH value of the system was adjusted to neutral and then precipitated with ethanol. Finally, carboxymethyl chitosan was obtained by centrifugation, suction filtration, and drying, and the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid was 10g:110mL:48g.
[0149] S2. Add aluminum nitrate nonahydrate to ethanol, stir evenly, then add ammonium fluoride and ethanolamine, and react under heating conditions (70°C, 6h). After the reaction is completed, heat up to remove excess ethanol, then carbonize (255°C, 1h), calcine (1000°C, 1.5h), and finally wash and dry to obtain modified alumina; wherein the amount ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10g:55mL:0.4g:1.6g;
[0150] S3, adding bentonite to water, stirring evenly under heating conditions (75°C), then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction (75°C, 8h), after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite; the amount ratio of bentonite, water, and tri-n-butyl phosphate is 10g:150mL:4.5g;
[0151] S4. Add the modified bentonite obtained in step S3 to water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35°C for 2h, then add the modified alumina obtained in step S2, continue stirring and heating for 2.5h, after the treatment is completed, centrifuge, filter, dry, crush and sieve 100 mesh to obtain a modified material; wherein the mass ratio of modified bentonite, water, carboxymethyl chitosan and modified alumina is 1:12:0.25:0.65.
[0152] Comparative Example 4
[0153] Compared with Example 1, in the preparation process of the modifier of Comparative Example 4, step S4 is omitted, that is, the bentonite is not modified. Specifically, Comparative Example 4 provides a rubber coating composite material, including the following preparation raw materials: 50 parts of methyl vinyl silicone rubber, 30 parts of high vinyl silicone rubber, 0.5 parts of organic peroxide, 5 parts of polyether modified polydimethylsiloxane, 10 parts of polyurethane elastomer, 18 parts of modifying material, 2 parts of triethoxysilane, 5 parts of tackifier, 15 parts of D4H cyclotetrasiloxane, 0.2 parts of platinum vulcanizer, and 0.15 parts of dispersant.
[0154] Wherein, the preparation of the modified material comprises the following steps:
[0155] S1, chitosan was added to a 40wt% sodium hydroxide solution, and chloroacetic acid was added in equal amounts three times under heating and stirring conditions (55°C). After the addition was completed, the heating temperature was maintained to continue the reaction (55°C, 4h). After the reaction was completed, the pH value of the system was adjusted to neutral and then precipitated with ethanol. Finally, carboxymethyl chitosan was obtained by centrifugation, suction filtration, and drying, and the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid was 10g:110mL:48g.
[0156] S2. Aluminum nitrate nonahydrate is added to ethanol, and ammonium fluoride and ethanolamine are added after stirring, and the reaction is carried out under heating conditions (70°C, 6h). After the reaction is completed, the temperature is first raised to remove excess ethanol, and then carbonization (255°C, 1h) and calcination (1000°C, 1.5h) are carried out in sequence, and finally washing and drying are carried out to obtain pre-modified alumina; wherein the amount ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10g:55mL:0.4g:1.6g;
[0157] S3, adding the pre-modified alumina obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating the reaction under stirring conditions (85°C, 2h). After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use; the amount ratio of pre-modified alumina, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1g:25g:1.2mL;
[0158] S4, take bentonite and set aside;
[0159] S5. Add the bentonite obtained in step S4 to water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35°C for 2 hours, then add the modified alumina obtained in step S3, continue stirring and heating for 2.5 hours. After the treatment is completed, centrifuge, filter, dry, crush and sieve 100 mesh to obtain a modified material; wherein the mass ratio of modified bentonite, water, carboxymethyl chitosan and modified alumina is 1:12:0.25:0.65.
[0160] Comparative Example 5
[0161] Compared with Example 4, Comparative Example 5 uses the rubber coating composite material prepared in Comparative Example 1, and the rest are the same.
[0162] Comparative Example 6
[0163] Compared with Example 4, Comparative Example 6 uses the rubber coating composite material prepared in Comparative Example 2, and the rest are the same.
[0164] Comparative Example 7
[0165] Compared with Example 4, Comparative Example 7 uses the rubber coating composite material prepared in Comparative Example 3, and the rest are the same.
[0166] Comparative Example 8
[0167] Compared with Example 4, Comparative Example 8 uses the rubber coating composite material prepared in Comparative Example 4, and the rest are the same.
[0168] The performance test of the rubber coating composite materials obtained in Example 1 and Comparative Examples 1 to 4 was carried out as follows:
[0169] The wear resistance is carried out in accordance with GB / T 1768-2006. After the coating is applied, it is first treated at 80°C for 2 minutes and then at 130°C for 3 minutes (the same below).
[0170] Weather resistance is carried out according to ISO 20340-2009.
[0171] The test results are shown in Table 1.
[0172] Table 1
[0173]
[0174] It can be seen from Table 1 that the rubber coating composite material prepared in the present invention has good wear resistance and weather resistance.
[0175] The flame retardant properties of the automotive leathers prepared in Example 4 and Comparative Examples 5 to 8 were tested, wherein the oxygen index test was performed with reference to ISO4589-1:2017, and the combustion grade was performed with reference to the vertical method of GB / T2408-2021.
[0176] The test results are shown in Table 2.
[0177] Table 1
[0178]
[0179] It can be seen from Table 2 that the automotive leather prepared in the embodiment of the present invention has good flame retardant properties.
[0180] Furthermore, the comprehensive performance test of the automobile leather prepared in Example 4 was carried out, and the test results are shown in Table 3.
[0181] Table 3
[0182]
[0183] It can be seen from Table 3 that the automotive leather material prepared by the present invention has good comprehensive performance and good market promotion and use value.
[0184] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A silicone rubber coating composite material, characterized in that: The preparation method comprises the following raw materials: 40 to 70 parts of methyl vinyl silicone rubber, 20 to 40 parts of high vinyl silicone rubber, 0.2 to 0.8 parts of organic peroxide, 2 to 8 parts of polyether modified polydimethylsiloxane, 5 to 15 parts of polyurethane elastomer, 8 to 25 parts of modified material, 1 to 5 parts of triethoxysilane, 2 to 8 parts of tackifier, 8 to 20 parts of D4H cyclotetrasiloxane, 0.1 to 1 part of platinum vulcanizer and 0.1 to 0.5 part of dispersant.
2. The silicone rubber coating composite material according to claim 1, characterized in that: The preparation of the modified material comprises the following steps: S1, chitosan is added to a sodium hydroxide solution, chloroacetic acid is added three times under heating and stirring conditions, and after the addition is completed, the heating temperature is maintained to continue the reaction. After the reaction is completed, the pH value of the system is adjusted to neutral and then precipitated with ethanol, and finally centrifuged, filtered, and dried to obtain carboxymethyl chitosan for standby use; S2, adding aluminum nitrate nonahydrate to ethanol, stirring evenly, then adding ammonium fluoride and ethanolamine, reacting under heating conditions, and after the reaction is completed, first heating to remove excess ethanol, then sequentially carbonizing and calcining, and finally washing and drying to obtain pre-modified alumina; S3, adding the pre-modified alumina obtained in step S2 to water, stirring evenly, then adding 3-(triethoxysilyl)propyl succinic anhydride, and then heating under stirring conditions for reaction. After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified alumina for standby use; S4, adding bentonite to water, stirring evenly under heating conditions, then adding tri-n-butyl phosphate, maintaining the heating temperature and continuing to stir the reaction, after the reaction is completed, centrifuging, washing, and drying to obtain modified bentonite; S5. Add the modified bentonite obtained in step S4 into water, stir evenly, then add the carboxymethyl chitosan obtained in step S1, heat and stir at 35-45°C for 1-4h, then add the modified alumina obtained in step S3, continue stirring and heating for 1-4h, after the treatment is completed, centrifuge, filter, dry, crush and sieve to obtain the modified material.
3. A rubber coating composite material according to claim 2, characterized in that: In step S1, the concentration of the sodium hydroxide solution is 30-50 wt %; The usage ratio of chitosan, sodium hydroxide solution and total amount of chloroacetic acid is 10g:90-150mL:40-60g; The three additions of chloroacetic acid were added in equal amounts; The heating temperature is 50-70°C and the reaction time is 2-6h.
4. The silicone rubber coating composite material according to claim 2, characterized in that: In step S2, the ratio of aluminum nitrate nonahydrate, ethanol, ammonium fluoride and ethanolamine is 10 g: 40-80 mL: 0.3-0.5 g: 1-2.5 g; The heating reaction temperature is 60-80°C and the reaction time is 3-10h; The carbonization temperature is 250-260°C and the carbonization time is 0.5-2h; The calcination temperature is 990-1050°C, and the calcination time is 0.5-4h.
5. The silicone rubber coating composite material according to claim 2, characterized in that: In step S3, the ratio of the pre-modified alumina, water, and 3-(triethoxysilyl)propyl succinic anhydride is 1 g: 20-30 g: 0.8-1.5 mL; The heating reaction temperature is 85-95°C, and the heating reaction time is 0.5-5h.
6. The silicone rubber coating composite material according to claim 2, characterized in that: In step S4, the usage ratio of bentonite, water and tri-n-butyl phosphate is 10 g: 120-200 mL: 3.5-5.5 g; The heating temperature is 70-85°C, and the stirring reaction time is 6-12 hours.
7. The silicone rubber coating composite material according to claim 2, characterized in that: In step S5, the mass ratio of modified bentonite, water, carboxymethyl chitosan, and modified alumina is 1:10-15:0.2-0.35:0.5-0.8; Sieve through 80-150 mesh.
8. Use of the silicone rubber coating composite material according to any one of claims 1 to 7 in the preparation of automobile leather.
9. A method for preparing automobile leather, characterized in that: The steps include: (1) After the silicone rubber coating composite material according to any one of claims 1 to 7 is uniformly mixed, the mixture is heated to 100 to 150 g / m 2 The amount is evenly coated on the release paper, and then baked in an oven to reach a semi-vulcanized state to obtain a coating surface layer; (2) Mix the filling layer formula evenly and add 120-180g / m 2 The amount of the coating is evenly applied to the surface of the coating obtained in step (1), and then baked in an oven to reach a semi-vulcanized state to obtain a filling layer; (3) Mix the bonding layer formula evenly and add 180-250g / m 2 The amount of the filling layer is evenly coated on the surface of the filling layer obtained in step (2), and after being baked in an oven, one side of the filling layer is bonded to the microfiber fabric, and after being baked again, it is completely vulcanized; (4) After the vulcanization is complete, the release paper is separated by a reeling machine to obtain the automotive leather product.
10. The method for preparing automobile leather according to claim 9, characterized in that: In step (1), the length of the oven is 10 m, the temperature of the four zones is 60° C., and the baking time is 2 min; In step (2), the filling layer formula includes the following raw materials, measured in parts by weight: 80-120 parts of methyl vinyl silicone rubber, 40-50 parts of fumed silica, 8-15 parts of hexamethylcyclotrisilazane, 2-8 parts of polyether modified polydimethylsiloxane, 0.2-1 parts of organic peroxide, 1-3 parts of triethoxysilane, 0.1-0.2 parts of white spirit, 0.1-0.2 parts of decanate, 0.5-1 parts of matting powder, and 0.08-0.2 parts of dispersant; The oven length is 15m, the temperature of the four zones is 80℃, and the baking time is 2min; In step (3), the laminating layer formula includes the following raw materials, in parts by weight: 80-120 parts of methyl vinyl silicone rubber, 40-50 parts of fumed silica, 8-15 parts of hexamethylcyclotrisilazane, 2-8 parts of polyether modified polydimethylsiloxane, 0.1-1 parts of organic peroxide, 1-3 parts of triethoxysilane, 0.1-0.2 parts of white spirit, 0.1-0.2 parts of decanate, 0.1-1 parts of platinum vulcanizing agent, 0.5-1 parts of matting powder, 0.5-1 parts of tackifier, and 0.08-0.2 parts of dispersant; The oven length after coating the laminating layer formula is 5m, the temperature of the four zones is 75°C, and the baking time is 30s; The length of the oven for the second baking is 35m, the baking temperatures in the five zones are 100°C, 100°C, 110°C, 120°C, and 130°C, and the baking time is 5min.
Citation Information
Patent Citations
High-performance environment-friendly micro-fiber automobile leather and preparation method thereof
CN109811557A
Organic silicon automobile leather capable of being bitten by mouths of infants and preparation method of organic silicon automobile leather
CN117002117A